Dari Ritual Ke Panggung Pertunjukan: Perkembangan Tari Dalam Kehidupan Masyarakat - Tati Narawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2004)
There are three primary functions of dance in human life, i.e., for ritual,for personal entertainment, and for aesthetic presentation. All dance experts believe that the oldest function of dance in human life is for ritual. Dance is needed on the occasion of birth, circumcision, marriage, death, war, changes of the moon and sickness. Bali is the richest island of dance in Indonesia and known as